(untitled) (Research, Society and Development, 2025)
The Brasília Pilot Plan, although recognized for its quality infrastructure and services, is home to a significant vulnerable population that often goes unnoticed. With around 220 thousand inhabitants, the region is considered developed, but it has the largest homeless population in the Federal District, highlighting the precarious health and access conditions. Vulnerability is linked to factors such as inadequate food, decent housing, sanitation and work and leisure opportunities. The main objectives of this study include understanding the habits and social and health conditions of vulnerable populations, mapping the territory of these populations in the Central Health Region of the Federal District and highlighting the existence of vulnerable populations in the country’s capital. The results indicate that social vulnerability in the central region of the country’s capital is present, even if discreetly and silently, in several areas throughout the Plano Piloto. A cross-sectional literature review of a qualitative nature was carried out on the topic.